Rhetorical Moves and Linguistic Realization: Corpus-Based Analysis of Bachelor Theses Abstracts in Islamic University - Nabu, Andiani Rezkita (Al-Lisan: Jurnal Bahasa, 2023)
Recently, studies on rhetorical moves in undergraduate students' abstracts have gained popularity. It has been the focus of several disciplines, techniques, and methods. However, research in bachelor thesis abstracts, particularly in Islamic universities as the research site, is rarely explored. The purpose of this research is to determine the rhetorical moves of undergraduate thesis abstracts and to explain the regularities of rhetorical moves at Islamic university. The analysis guideline was based on Hyland's (2004) theory, and the AntMover program was utilized to aid with the analysis. The findings revealed that, while the occurrence of moves and steps varies by data group, there are certain required, conventional, and discretionary moves. Furthermore, this study discovered many sorts of rhetorical organization generated by the occurrences of moves and steps in students' abstracts. Some are in regular forms, while others are in irregular shapes. As a result, this study sheds light on the gap in rhetorical motion patterns in student abstracts. Then, certain proposals were made to bridge the gap in improving the quality of students, study programs, and institutions in general.